Kinerja Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Gianyar dalam Meningkatkan Kesejahteraan Masyarakat - Ni Putu Anik Prabawati; Ni Wayan Supriliyani (Bahasa Indonesia, 2020)
Abstract This study aims to determine the performance of the Gianyar Regency Community and Village Empowerment Service in improving the welfare of the community in the Gianyar regency. Knowing the programs implemented in deceiving the community and the realization of these programs. In obtaining these data, this study uses qualitative research methods. The results of the study state that the Community and Village Empowerment Service has implemented performance in accordance with the provisions of the performance measurement indicators in empowering the community. There are various types of development and empowerment programs implemented to encourage the development of the creative industry in society. The conclusion of this study is that the performance of the Community and Village Empowerment Service has been effective in improving the welfare of the community in Gianyar Regency. Keywords: Community; Empowerment; Welfare